Optimal placement of recloser for the improvement of reliability indices in radial distribution system using hybrid PSO-firefly algorithm - Ogunjuyigbe, Jacob Kehinde; Ashigwuike, Evans Chinemezu; Araoye, Timothy Oluwaseun; Aina, Oluyinka Olugbenga; Ozulu, Onyekachukwu Denis; Ibrahim, Sardauna; Onuh, Issac Ojochogwu; Mbamalu, Ikenna Chuddy (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
Electricity outages are frequently caused due to problems in the electric distribution system (EDS). The method presented in this research describes a comprehensive dual-phased designed to enhance the electric network efficiency and reliability. A hybrid particle-firefly optimization method is applied in the first phase to allocate reclosers and sectionalizer in an optimal accessible path. Furthermore, in the second phase, the Medium distribution voltage Systems that comprises five main circuit breaker and one power source are taken into consideration, as well as automatic  load shift to an alternative power supply and the secondary circuit breaker shut down under normal conditions. The authors provide a streamlined technique based on swapping out loads discrete to determine the reduction value of the anticipated energy not-supplied (ENS) and cost of energy not-supplied (CENS) to customers after installing sectionalizer and recloser in APO radial substation network. The optimized CENS with protective device of the distribution system is tremendously reduce compared to the CENS of the conventional state which has no protective scheme.